2019
DOI: 10.1161/hypertensionaha.118.12150
|View full text |Cite
|
Sign up to set email alerts
|

Multilayered Interplay Between Fructose and Salt in Development of Hypertension

Abstract: T he prevalence of hypertension escalated over the past decades reaching an epidemic level worldwide. 1 Currently, the prevalence of hypertension is ≈30% of the adult US population, according to the National Health and Nutrition Examination Survey data, with many of these subjects having insulin resistance and or other features of the metabolic syndrome. 2 In this regard, dietary fructose from sucrose or high-fructose corn syrup (HFCS) in food and beverages has been convincingly linked with hypertension in lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 120 publications
0
15
0
Order By: Relevance
“…The administration of high NaCl content (8% NaCl) for 2 weeks increased systolic blood pressure, plasma glucose levels, and liver gluconeogenesis [ 6 ]. Recent studies have suggested that a high-salt diet activates processes that result in fructose generation in the liver (endogenous fructose production) [ 46 ].…”
Section: Development Of Mets Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The administration of high NaCl content (8% NaCl) for 2 weeks increased systolic blood pressure, plasma glucose levels, and liver gluconeogenesis [ 6 ]. Recent studies have suggested that a high-salt diet activates processes that result in fructose generation in the liver (endogenous fructose production) [ 46 ].…”
Section: Development Of Mets Modelmentioning
confidence: 99%
“…A high-salt diet will activate tonicity-responsive enhancer binding protein (TonEBP), a transcription factor that promotes kidney inflammation and osmolyte production in response to inflammation and osmotic stress. In turn, TonEBP activates the aldose reductase pathway, leading to endogenous fructose generation; this indicates a complex interplay in which salt and fructose synergize together to raise blood pressure ( Figure-4 ) [ 46 ].…”
Section: Development Of Mets Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperuricemia prevalence also displays an increasing parallel tendency similar to that of noncommunicable diseases. The increase in hyperuricemia is believed to originate from diet changes and high fructose consumption in both low-income and developed countries (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…The consumption of high-fructose corn syrup can have unfavorable effects including weight gain, insulin resistance, hypo-high-density lipoprotein cholesterolemia, and hypertriglyceridemia [3, 4]. Fructose from sucrose or high-fructose corn syrup enhances salt absorption in the gut and kidney and enhances intracellular angiotensin formation [5], whereas the fructose contained in fruits does not raise blood pressure because fruits’ high potassium, antioxidant vitamins such as vitamin C, various flavonols, and dietary fiber protect against this fructose-induced effect on blood pressure [6].…”
mentioning
confidence: 99%